2013
DOI: 10.1080/10615806.2013.828202
|View full text |Cite
|
Sign up to set email alerts
|

Psychological resilience: the impact of affectivity and coping on state anxiety and positive emotions during and after the Washington, DC sniper killings

Abstract: This research examined the impact of affectivity and coping on state anxiety and positive emotions among young adults living in the Washington, DC metro area both during and after the Washington, DC sniper killings. Participants completed questionnaires during three waves of data collection: (1) during the sniper attacks (n=92); (2) within two weeks after the snipers were captured (n=45); and (3) six months later (n=43). Affectivity (measured by neuroticism) was significantly associated with state anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…Costa and McCrae (1989) obtained a scale of NEO Five-Factor Inventory (NEO-FFI) including 60 items based on NEO-PI, which was used to measure five personality structures, such as neuroticism, conscientiousness, extraversion, agreeableness, and openness. Considering that neuroticism in personality had been proven to be a powerful predictor of anxiety in previous studies (Moore et al, 2014;Xin et al, 2014), in order to exclude the influence of neuroticism, the neuroticism subscale was used in this study. The scale included 12 items, each with five levels, from "strongly opposed" to "very supportive."…”
Section: Multidimensional Scale Of Perceived Social Supportmentioning
confidence: 99%
“…Costa and McCrae (1989) obtained a scale of NEO Five-Factor Inventory (NEO-FFI) including 60 items based on NEO-PI, which was used to measure five personality structures, such as neuroticism, conscientiousness, extraversion, agreeableness, and openness. Considering that neuroticism in personality had been proven to be a powerful predictor of anxiety in previous studies (Moore et al, 2014;Xin et al, 2014), in order to exclude the influence of neuroticism, the neuroticism subscale was used in this study. The scale included 12 items, each with five levels, from "strongly opposed" to "very supportive."…”
Section: Multidimensional Scale Of Perceived Social Supportmentioning
confidence: 99%
“…Good constructive thinkers react less defensively and appraise events more positively than poorer constructive thinkers, leading to less cognitive distortion (Epstein & Meier, 1989; Scheuer & Epstein, 1997). Although researchers have only recently begun to examine the role of constructive thinking in the context of highly stressful events (e.g., Moore et al, 2014), researchers have long demonstrated that constructive thinking relates to less distress following laboratory stressors and daily life stressors (e.g., Katz & Epstein, 1991; Park & Grant, 2005)…”
Section: Coping Ability As a Potential Moderator Of The Trauma Centra...mentioning
confidence: 99%
“…Resilience also has a positive influence on psychological coherence, subjective well-being, positive emotions, proactive coping behaviors, or cohesive relationships (Moore et al, 2014), and is inversely linked with psychological distress (Lee et al, 2018;Osofsky et al, 2011). Connor and Davidson (2003) consider resilience as a measure of people's ability to successfully cope with the stress produced by an adverse situation.…”
Section: Introductionmentioning
confidence: 99%